Increased risk during winter: common respiratory viruses and clinical outcomes in hospitalized children - Furkan Kalayci; Aslinur Ozkaya Parlakay; Metin Yigit; Gamze Nur Güler; Betül Demircioglu Kalayci; Aybuke Nur Cetin; Merve Dervisoglu Yurteri; Ece Karakose; Kaan Celebier; Naci Yilmaz; Orkun Tolunay (BMC Infectious Diseases)
Abstract Background Acute respiratory infections (ARIs) are a leading cause of hospitalisation, severe morbidity, and mortality in children, representing a significant public health concern. This study aimed to evaluate the clinical features, laboratory findings, and outcomes of pediatric patients hospitalised due to ARIs caused by common respiratory viruses, including influenza virüs (IFV), human bocavirus (hBoV), human metapneumovirus(hMPV), human rhinovirus (hRV), and human respiratory syncytial virüs (hRSV). Methods We conducted a retrospective analysis of 1465 hospitalized pediatric patients at Ankara Bilkent City Hospital Children’s Hospital between August 2019 and March 2024. Nasopharyngeal swabs were analyzed using multiplex real-time PCR to identify viral pathogens. Clinical data, including demographics, intensive care needs, respiratory support, and chronic health conditions, were reviewed. Results A total of 1465 hospitalized children were included in the study, with a median age of 3 years and 61.8% being male. Of these patients, 32.9% (n = 482) had chronic health conditions. IFV was detected in 30.1% of patients, hBoV in 28.3%, hRSV in 18.4%, hRV in 14.4%, and hMPV in 8.8%. Over half of the infections occurred during the winter months, with IFV being the most commonly observed virus. Fever was most frequently observed in IFV cases, while cough and hypoxia were more prevalent in hBoV and hRSV infections. Admission to the Pediatric Intensive Care Unit was necessary in 19.5% of cases, with 33.1% of these requiring invasive mechanical ventilation. Invasive mechanical ventilation was most frequently required in hBoV cases. The mortality rate was 8.7%, predominantly observed in patients with chronic health conditions; hBoV was associated with the highest mortality. Conclusion This study provides a comprehensive analysis of the clinical, laboratory, and radiological characteristics of children hospitalized due to viral lower respiratory tract infections, offering valuable insights into common respiratory pathogens. The findings underscore a higher incidence of these infections during the winter months. It is recommended that hBoV and IFV infections be closely monitored in children with underlying chronic conditions. Moreover, the study highlights the importance of meticulous management of hBoV and hRSV infections, given their association with an increased need for intensive care support.